Effect of idling on fuel consumption and emissions of a diesel engine fueled by Jatropha biodiesel blends - Rahman, S.M. Ashrafur; Masjuki, H.H.; Kalam, M.A.; Abedin, M.J.; Sanjid, A.; Imtenan, S. (Journal of cleaner production, 2014)
An engine running at low load and low rated speed is said to be subject to high idling conditions, a mode which represents one of the major problems currently the transport industry is facing. During this time, the engine can not work at peak operating temperature. This leads to incomplete combustion and emissions level increase due to having fuel residues in the exhaust. Also, idling results in increase in fuel consumption. The purpose of this study is to evaluate fuel consumption and emissions parameters under high idling conditions when diesel blended with Jatropha curcas biodiesel is used to operate a diesel engine. Although biodiesel–diesel blends decrease carbon monoxide and hydrocarbon emissions, they increase nitrogen oxides emissions in high idling modes. Compared to pure diesel fuel, fuel consumption also increases under all high idling conditions for biodiesel–diesel blends, with a further increase occurring as blend percentage rises. •Jatropha biodiesel properties within ASTM limit.•At idling condition, Jatropha biodiesel reduces CO and HC emissions.•Increase in blend percentages results in significant reduction in CO and HC emissions.•Fuel consumption and NOx emissions deteriorates with the use of biodiesel blends.